Evaluation of polyurethane foam materials as air filters against fungal contamination. (March 2017) - Briffa, Mark; Decelis, Stephen; Brincat, Jean-Pierre; Grima, Joseph N.; Gatt, Ruben; Valdramidis, Vasilis
Abstract: Current air filters used in food processing or storage facilities are expensive and disposable. The ability to use polyurethane foam as air filters against fungal spores would be beneficial as they are both cheap and re-usable. The aim of this study was to evaluate the air filtration capabilities, in terms of fungal spores, of a selection of polyurethane foam(s) of differing combinations of pores per inch (PPI) (50 and 90 PPI) and thickness (15 and 20 mm). Environmental air was used as a source of fungal spores and membrane filtration was used to assess the filtration capabilities of the foams. Spores capable of passing through the foams were captured on cellulose nitrate membrane filters and quantified in CFU counts. Apart from the 50 PPI foam of 15 mm thickness, all the foam samples were effective at significantly reducing the number of spores. The PPI was found to be 2 times more influential on the efficiency of the foam material than the foam thickness. This may be explained through the higher number of pores present and the decrease in thickness of the ribs composing the microstructure of the foam as shown through scanning electron microscope (SEM) micrographs. These studies show that reticulated polyurethane foams at the selected PPI and thickness can be used as effective air filters against fungal spores. Highlights: The pores per inch and thickness of foams are important parameters. Reticulated polyurethane foams can be used as effective air filters. Temperature or relative humidity have no effect on the filtration efficiency.